The effects of climate on Engelmann spruce regeneration and vigor - Prolic, Curtis, author; Ex, Seth, advisor; Battaglia, Michael, committee member; Sibold, Jason, committee member (Colorado State University. Libraries, 2017)
Recent climate modeling suggests that drought will become more frequent in the southern Rocky Mountains over the next century. Understanding how tree species will respond and adapt to this changing climate is vital to guide future management decisions by land managers. Future increases in drought frequency and severity will likely have an impact on the composition of forests. Modeling studies have been used to predict the effect that increasing drought will have on Engelmann spruce in southwest Colorado, but little field data has been gathered to validate this modeling. This study uses empirical data to test whether drought conditions are related to decreases in seedling establishment and tree vigor. Annual regeneration data from 1990 to 2009 was collected from 24 sites with 30-year PRISM precipitation normals ranging from 531 mm to 924 mm to determine if dry and wet sites respond differently to drought. Elevations of our study sites ranged from 3100 m to 3500 m above sea level. Among these 24 sites, we found the number of seedlings per hectare varied between 1804 and 18975. We used a mixed effects model to identify climate variables important to annual seedling establishment density. A separate provenance study on the White River National Forest was analyzed to identify drought effects on tree vigor. Engelmann spruce bareroot seedlings from twenty sources ranging from British Columbia to New Mexico were planted in 1970 at an elevation of 2930 m north of Vail, Colorado. Annual precipitation normals of the 20 seed sources ranged from 423 – 1918 mm. We collected increment cores from six to eight trees from each of the 20 seed sources in 2016, and standardized the chronology of each tree using standard dendrochronological techniques. We then analyzed the annual radial growth response of each provenance to a period of severe drought from 2000-2004 using both RWI and a resistance/resilience framework. For both parts of our study, we found weather variability and drought did not impact regeneration or vigor as much as hypothesized, suggesting regeneration and vigor of spruce in these high elevation forests are not reduced by contemporary levels of drought.